1992
DOI: 10.1017/s0007123400006487
|View full text |Cite
|
Sign up to set email alerts
|

How to Win a Televised Debate: Candidate Strategies and Voter Response in Germany, 1972–87

Abstract: This article analyses candidates' strategies in leadership debates and voters' responses to those strategies. Based on an examination of German election campaign debates since 1972, we specify a number of different debating strategies available to the candidates. The strategic choices made by each party leader are then identified through content analysis. Finally, employing aggregate-level data, regression models are used to determine whether or not the debaters' strategies influenced voters' evaluations of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…One possible explanation for this result is that a speaker who is able to keep from fighting back or from getting flustered or angry despite a rude opponent seems especially respectful and appropriate to audience members. Whatever the case, our results are consistent with previous research indicating that debaters who are verbally attacked tend to benefit, perhaps because voters frown upon such negative behaviors (Schrott & Lanoue, 1992). Our results are also consistent with a study by Beatty and Kruger (1978) that indicated that, when an audience identified with a heckled speaker, the speaker was more effective.…”
Section: Discussionsupporting
confidence: 91%
“…One possible explanation for this result is that a speaker who is able to keep from fighting back or from getting flustered or angry despite a rude opponent seems especially respectful and appropriate to audience members. Whatever the case, our results are consistent with previous research indicating that debaters who are verbally attacked tend to benefit, perhaps because voters frown upon such negative behaviors (Schrott & Lanoue, 1992). Our results are also consistent with a study by Beatty and Kruger (1978) that indicated that, when an audience identified with a heckled speaker, the speaker was more effective.…”
Section: Discussionsupporting
confidence: 91%
“…These results indicate this study may have especially important applications in close debates. Indeed, as Schrott and Lanoue (1992) noted, in extremely close contests, even minor factors can influence the outcome of a debate. The present study implies that the background behavior of debaters might constitute one such factor.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, they indicated that South Korean candidates used general goals and ideals more to acclaim than to attack. Some research on non-U.S. debates, as noted earlier, studied audience effects of debates (Jorgensen et al, 1998;Schrott and Lanoue, 1992). Several studies (e.g., many of the chapters in Asard and Gronbeck, 2000;Coleman, 2000) are designed as historical or conceptual analyses rather than studies of the content of these debates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, meta-analysis found that presidential debates can have several effects on voters, creating issue knowledge, influencing perceptions of the candidatesÕ character, and at times altering vote choice (Benoit et al, 2003a). Studies conducted on non-U.S. debates confirms that effects can occur from both issue (Jorgensen et al, 1998) and candidate (Baker and Norpoth, 1981;Blais and Boyer, 1996;Faas and Maier, 2004;Lanoue, 1991;Schrott, 1990;Schrott and Lanoue, 1992) debates. There is no doubt that televised political debates around the world merit scholarly attention as an important form of public argumentation.…”
Section: Introductionmentioning
confidence: 96%